Recommendation, class repeating, and children's ability: German school tracking experiences - Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2008)
While the 2006 Progress in International Reading Literacy Study assesses the average ability of German primary school students as being higher than average, the Programme for International Student Assessment studies (2000, 2003, 2006) ranks German secondary school students at a considerably lower level. Using data from the German Socio-Economic Panel, this paper examines whether a teacher's recommendation for the secondary school track and class repeating are causes for these ability differences. According to the estimates, failures as a result of teachers'recommendations given at the end of primary school are an important reason for the differences between the two types of studies. Being required to repeat a school class amplifies the inefficient management of children's abilities. In addition, we find evidence that regional economic performance at the time the recommendation is made affects the decision for the tracking path.
Keywords: I21; J28; J1; 330; education attainment; school system; educational tracking; Kinder; Bildungsniveau; Bildungsverhalten; Leistungsprinzip; Schulpolitik; Deutschland